PEREMPUAN DAN MATEMATIKA - Makkulau, Makkulau (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
Gender gap was influenced mathematical ability between boys and girls. Stereotypes about women’s position lower in mathematics is a contrasting landscape and different from the data and scientific facts. The result of re- search in 69 countries with gender equality shows that teenage girls tend to have a math test scores higher. In addition, young women also tend to do about the matter of better and more confident in their ability in the field of math. The results of this study also showed that young women have the same ability with young men when they are given an equal education, espe- cially in mathematics.Keywords: kesenjangan gender, matematika, stereotip, data dan fakta ilmiah.